Answers

2015-08-15T08:57:16+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
 x^{3}-3 x^{2} -9 x-5

we are putting x=1
sol. = 1-3-9-5 = -16 is not eql to 0.
x= -1
-1 -3 +9 -5 = 0 
hence x= -1 is one sol. of our cubic eqn.
now divide  x^{3}-3 x^{2} -9 x-5 by x + 1
divident =  x^{2} - 4x - 5

sol. of eqn. x-5 nd x+1

hence all three sol. of eqn are:- x=-1 , x = 5 , x = -1

happy independence day..


0
2015-08-15T12:32:24+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
X3-3X2-9X-5
BY PITTING -1 POLY. BEcome 0
therefore (x+1)is a factor
now divide poly. by (x+1)
we get(x2-4x-5)
now factorise itand get the ans
0